RATIO LEGIS OF THE PROVISION OF SOCIAL WORK CRIMINAL SANCTIONS IN LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE - M. Fachryan Arief; Saiful Abdullah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Social work punishment is one of the non-imprisonment alternative punishment threats accommodated in Article 85 paragraph (8) of Law Number 1 Year 2023 on the New Criminal Code (KUHP). This provision creates changes in the punishment system in Indonesia. The purpose of the criminal sanction of social work is to provide guidance and mentoring in order to become a good and useful person, especially since the punishment is not intended to degrade human dignity. However, efforts to realize this goal must be carried out through a clear and precise mechanism for the implementation of social work punishment, but the New Criminal Code has not clearly established the mechanism or institution responsible for the implementation of social work punishment. On this basis, this study aims to analyze the ratio legis (purpose) of the regulation of social work punishment in the New Criminal Code and recommend the concept of ideal implementation supervision arrangement in the future. This type of research is normative and the results conclude: First, social work punishment is regulated due to the occurrence of over capacity and is considered ineffective as a coaching space. Second, the ideal concept of the implementation of social work punishment to support the purpose of punishment is not only sufficiently carried out by law enforcement officials and/or Correctional Institutions, but the involvement of social institutions and other institutions will provide a more optimal correctional influence.